2017
DOI: 10.1071/rj16014
|View full text |Cite
|
Sign up to set email alerts
|

A woody plant community and tree-cacti associations change with distance to a water source in a dry Chaco forest of Argentina

Abstract: In semiarid regions, livestock is concentrated around water sources generating a piosphere pattern (gradients of woody vegetation degradation with increasing proximity to water). Close to the water source, livestock may affect the composition, structure and regeneration strategies of woody vegetation. We used the proximity from a water source as a proxy of grazing pressure. Our objectives were (1) to compare woody vegetation attributes (richness, diversity, species composition, density and basal area) and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(71 reference statements)
1
5
0
1
Order By: Relevance
“…The same response was observed in dry forest ungrazed during 7-8 years [46]. However, other studies have shown that heavy grazing modifies richness, density, and species diversity of woody plants [47,48], as well as spatial distribution [49], reduction in tree emergence, and survival [50].…”
Section: Discussionsupporting
confidence: 63%
“…The same response was observed in dry forest ungrazed during 7-8 years [46]. However, other studies have shown that heavy grazing modifies richness, density, and species diversity of woody plants [47,48], as well as spatial distribution [49], reduction in tree emergence, and survival [50].…”
Section: Discussionsupporting
confidence: 63%
“…Shrubs can provide an important source of fruits for wildlife (Caziani and Protomastro, 1994;Ponce et al, 2012), or offer forage biomass for native and domestic herbivores (Bucher, 1987;Catan and Degano, 2007;Cora et al, 2005;Quiroga and Esnarriaga, 2014). Also, shrubs can promote regeneration niches that other plants can use for their establishment, growth and survival (Barchuk et al, 2005;Caccia et al, 2009;Tálamo et al, 2015aTálamo et al, , 2015bTrigo et al, 2017). Understanding how forestry affects understory vegetation structure and the regeneration of timber species is key to assess the sustainability of logging and measure potential consequences to ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
“…Canopy closure was measured at four different points along each transect (0, 16, 33, and 50 m) using a spherical densiometer (Paletto & Tosi, ). We sampled vertical structure at the same four points (0, 16, 33, and 50 m) on each transect, by holding up a 2‐m telescopic rod (marked at 1‐m intervals and extensible up to 15 m) and recording the number and height of contacts of woody vegetation on the rod (Lopez de Casenave, Pelotto, Caziani, Mermozand, & Protomastro, ; Trigo et al, ). Although tree height varied between sites from around up to 20 m in Yacutinga (pers.…”
Section: Methodsmentioning
confidence: 99%